2016
DOI: 10.1111/vec.12510
|View full text |Cite
|
Sign up to set email alerts
|

The effect of storage on ammonia, cytokine, and chemokine concentrations in feline whole blood

Abstract: Ammonia concentration increases with storage time in feline SWB. The clinical significance of this finding is yet to be determined. The presence of the proinflammatory chemokine CXCL-8 in feline SWB warrants further research to determine whether it can incite an inflammatory response in the recipient. Further research evaluating the epidemiology of transfusion reactions in cats should evaluate the effect of unit age, and should include the possible impact of the presence of CXCL-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…A prospective ex vivo study by Cummings et al . () revealed increased concentration of the proinflammatory chemokine ligand 8 (CXCL‐8) in RBC units during storage, similar to studies in humans (Stack et al . , Kristiansson et al .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A prospective ex vivo study by Cummings et al . () revealed increased concentration of the proinflammatory chemokine ligand 8 (CXCL‐8) in RBC units during storage, similar to studies in humans (Stack et al . , Kristiansson et al .…”
Section: Discussionsupporting
confidence: 83%
“…During storage, erythrocytes undergo biochemical, biomechanical and immunologic changes that may compromise RBC survival and function, making the transfusion less effective and possibly adversely impacting the recipient (Obrador et al 2015, Heinz et al 2016. Several studies have documented storage lesions in feline RBC products over time (Aubert et al 2011;Cummings et al 2016;Heinz et al 2016;Blasi et al Blasi Brugué et al 2018), although the impact of storage times has not been evaluated in feline transfusion recipients. A prospective ex vivo study by Cummings et al (2016) revealed increased concentration of the proinflammatory chemokine ligand 8 (CXCL-8) in RBC units during storage, similar to studies in humans (Stack et al 1995, Kristiansson et al 1996 and dogs (Corsi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two recent studies aimed to evaluate storage lesions in feline pRBCs [ 11 , 12 ]. Significant supernatant increases of lactate, ammonia, sodium and chloride, and decreases of glucose and potassium levels were described.…”
Section: Discussionmentioning
confidence: 99%
“…During storage, blood cells maintain their metabolic activity, releasing byproducts to the media and suffering from biologic and immunologic changes, which may affect red blood cells (RBCs) function and survival. These changes are known as storage lesions, and may cause adverse effects on the recipients [ 4 , 7 11 ]. Haemolysis, as one result from these processes, may be regarded as an indicator of storage lesions.…”
Section: Introductionmentioning
confidence: 99%